Pendekatan zachman framework untuk Integrasi Tatakelola Sistem Informasi Perguruan Tinggi - Muhammad Hatta (LPPM Universitas Al Asyariah Mandar, 2015)
Strategy governance systems integration and information technology in a college is very important to improve competitiveness in the progress of science and technology today. Management of information technology should be planned and put in the form of information technology planning blueprint so that universities can prevent or minimize unwanted things. Enterprise architecture is a tool that is used for defining the enterprise organization in the form of information technology blueprint, the Zachman enterprise architecture framework approach is a systematic and comprehensive manner pendefinisikan aspects should be explored and identified, which are grouped based on the perspective and focus of the study. The aspects mentioned can be mapped into contextual architecture, conceptual, data, applications, and technologies. The design of this blueprint provides guidance in the use of systems and information technology for the college. Blueprint produced is used as a reference set policy college strategic plans, policies in determining the rules, policy governance system integration strategy and information technology, and investment policies in the application of information technology. This policy aims to increase the business value and create competitive advantage universities